Data and methods in the environment-migration nexus: a scale perspective - Eklund, Lina; Romankiewicz, Clemens; Brandt, Martin; Doevenspeck, Martin; Samimi, Cyrus (DIE ERDE: Journal of the Geographical Society of Berlin, 2016)
The relationship between environment and migration has gained increased attention since the 1990s when the Intergovernmental Panel on Climate Change projected climate change to become a major driver of human migration. Evaluations of this relationship include both quantitative and qualitative assessments. This review article introduces the concept of scale to environment-migration research as an important methodological issue for the reliability of conclusions drawn. The review of case studies shows that scale issues are highly present in environment-migration research but rarely discussed. Several case studies base their results on data at very coarse resolutions that have undergone strong modifications and generalizations. We argue that scale-related shortcomings must be considered in all stages of environment-migration research.